2018
DOI: 10.1080/00220388.2017.1400015
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Value-Added Tax on Revenue and Inequality

Abstract: This paper examines the impact of the introduction of the value-added tax on inequality and government revenues using newly released macro data. We present both conventional country fixed effect regressions and instrumental variable analyses, where VAT adoption is instrumented using the previous values of neighbouring countries' VAT systems as an instrument. The results revealin contrast to earlier workthat the revenue consequences of the VAT have not been positive. The results indicate that income-based inequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 34 publications
2
51
0
2
Order By: Relevance
“…The loss of income tax revenues will compensate for the growth of indirect tax revenues. Alavuotunki et al (2019) state that income-based inequality has increased due to VAT adoption. Lin & Jia (2019) recommends that tax cuts will have a favorable implication for the economy if a country has reached the top of the Laffer curve.…”
Section: Methodsmentioning
confidence: 99%
“…The loss of income tax revenues will compensate for the growth of indirect tax revenues. Alavuotunki et al (2019) state that income-based inequality has increased due to VAT adoption. Lin & Jia (2019) recommends that tax cuts will have a favorable implication for the economy if a country has reached the top of the Laffer curve.…”
Section: Methodsmentioning
confidence: 99%
“…These findings are divergent to the outcome of this study that revealed a positive relationship between tax gap realized and capital expenditure on economic services. Alavuotunki, Haapanen and Pirttilä (2019) reported that Value Added Tax caused inequality in income base and there was no effect on consumption inequality, this result is in contrast to Sok-Gee, Zulkufly and Mohd Zaini (2017) who noted that Value Added Tax enhanced government spending on economic growth and that government spending promotes economic growth. The outcome of this study aligns with the position of Sok-Gee, Zulkufly, and Mohd Zaini (2017).Adegbite, (2018); Onuora, Okegbe and Ezejiofor (2017); Ibadin and Oladipipo (2016) all agreed with empirical evidence thatValue Added Tax is significant in the Nigerian economy.Results from the studies revealed that Value Added Tax had an overall significant effect on Economic growth and this position aligns with the outcome of this study.…”
Section: Diagnostic Testmentioning
confidence: 73%
“…Peralta-Alva et al (2018) found that in lowincome countries, value added tax (VAT) has the least efficiency costs but is highly regressive, while personal income tax (PIT) impacts the economy in the opposite way with corporate income tax (CIT) impacts staying in between. Alavuotunki, Haapanen, and Pirttil (2018) revealed that the revenue consequences of the VAT have not been positive, indicating that income-based inequality has increased due to the VAT adoption, whereas consumption inequality has remained unaffected.…”
Section: Literature Reviewmentioning
confidence: 99%